Validation of the Amsterdam Pre-surgery Anxiety and Information Scale in Latino American women with breast cancer: Mexico – Costa Rica research - Méndez-Meneses, Karla Janeth; Rebolledo García, María Luisa; Díaz Chacón, Stephanie; Rodríguez Vázquez, Luis Alberto; Acosta Maldonado, Brenda Lizeth; Mantilla-Maya, Blanca; González-Rodríguez, Eva; Aguilar Ponce, José Luis; Galindo Vázquez, Oscar; Rivera-Fong, Liliana (Psicooncología, 2019)
Surgery is the most frequent and efficient treatment for cancer, however, it is an invasive procedure that has been associated with psychological symptoms in up to 76% of patients. Health professional require specific and adapted tools to evaluate anxiety related to surgery, but there are few instruments to evaluate it. An option is the Amsterdam Preoperative Anxiety and Information Scale (APAIS), which has been validated in multiple countries with patients undergoing different surgeries. Validations have shown APAIS has adequate psychometric properties. Aim: To obtain the reliability and validity of APAIS in the oncology population for the Latin American population. Method: Cross-sectional, non-experimental, psychometric analysis study that included a non-probabilistic sample of 117 women aged between 25 and 75 years, all patients have been diagnosed with breast cancer and have been scheduled for surgery in a public hospital in Mexico (57 women) or Costa Rica (63 women). Results: The six items of the APAIS Scale showed an adequate distribution of the responses of the participants among the response options, the ability to discriminate between extreme groups and contributed to the internal consistency of the instrument. The factor analysis of maximum likelihood with varimax rotation showed a structure that explained 58.58% of the variance with two factors, this structure was confirmed by a confirmatory factor analysis. The total scale showed an internal consistency of α = .816. This scale showed adequate sensitivity and specificity with a cut-off point of 14 points. Conclusions: The APAIS scale shows adequate psychometric properties to be considered valid and reliable to evaluate pre-surgical anxiety in patients with cancer.